Analfabetismo digital en el campo laboral ecuatoriano - Molina Del Pozo, María José (2019)
The objective and purpose of this research is to show how digital illiteracy affects the search for employment and the labor field in Ecuador. Although Ecuador wants to become a fully digitalised country, it still has a long way to go to integrate into the digital world. It also seeks to expose the impact that not finding a job because of digital illiteracy can have. The research focuses on the analysis of the results achieved by Ecuador in terms of digital literacy courses, such as the creation of Megainfocenters and Infocenters in the country and courses carried out by the Municipality of Quito. It is important to know what is happening in Ecuador in terms of digital strategies and how it affects socially. During the development of this research we have considered: statistical data, interviews and statements from different fields, such as: public institutions, government, people affected by digital illiteracy.